SYNTHESIS OF TETRACYCLINE IMPRINTED POLYMERS WITH METHACRYLIC ACID AS FUNCTIONAL MONOMER IN METHANOL-CHLOROFORM MIXTURE USING BULK AND PRECIPITATION POLYMERIZATION METHOD - Suryana, Shendi; Shabrina, Kharisma Devy; Soni, Dang (Jurnal Ilmiah Farmako Bahari, 2024)
The content of tetracycline residues in poultry meat products can cause antibiotic resistance in humans who consume these products, so it is necessary to develop sensitive analytical techniques to determine the levels of tetracycline residues to assess the safety of these products for consumption. The molecular imprinting technique is a method to produce sorbents with molecular recognition capability of target compounds that can be used to increase the selectivity of solid phase extraction to extract tetracycline residues for further analysis. This study aimed to obtain a sorbent synthesized by molecular imprinting technique to analyze tetracycline in poultry meat products. The stages of the research began with the study of the interaction of functional monomers with template molecules, determining the association constants of functional monomers with template molecules, synthesis of imprinted polymer molecules using bulk and precipitation methods, evaluating the ability and adsorption capacity of the synthesized polymers, assess the selectivity of polymers for analog structures and physical characteristics with FTIR. The research showed that methacrylic acid was the best functional monomer with a binding energy value of -27.3776 kcal/mol. The higher adsorption capacity was achieved by Molecularly Imprinted Polymer (MIP) that was synthesized by precipitation method (MIP2) than the other MIP synthesized by bulk polymerization (MIP1) with a value of 0.8748 mg/g and 0.4077 mg/g, respectively. The analogous compounds' imprinting factor values for each MIP were 1.197 and 1.1272. The polymer synthesized by molecular imprinting technique is selective for extracting and analyzing tetracycline from poultry meat matrix.